Comparison of macrofaunal assemblages in temperate seagrass meadows and neighboring seabeds along the southeastern coast of Shandong Peninsula, China. (May 2023) - Bi, Peiru; Chen, Guangcheng; Wang, Jiming; Hu, Hongzhi; Jiang, Zengjie; An, Wenshuo; Zhang, Jing; Wang, Jing; Liu, Xiaoshou
Abstract: Comparative study of macrofaunal assemblages in seagrass meadows and neighboring seabeds along the southeastern coast of Shandong Peninsula, China were performed. A total of 136 species were identified, including polychaetes (49 species), crustaceans (28), molluscs (58), and echinoderms (1). Species numbers of macrofauna in seagrass meadows and the neighboring seabeds were 52 and 65, respectively, whereas those in autumn were 90 and 56, respectively. Average macrofaunal abundances in spring in seagrass and neighboring seabeds were 2388.9 and 2516.7 ind./m 2, respectively, whereas those in autumn were 11, 689.0 and 1733.3 ind./m 2, respectively. Ranges of species richness index, evenness index, and Shannon-Wiener index in seagrass meadows and the neighboring seabeds were 1.3–2.7, 0.7–0.9, 2.8–3.8, and 1.04–2.4, 0.5–0.9, 1.6–3.4 during spring, whereas those in autumn were 0.1–4.2, 0.3–0.8, 0.8–3.6 and 1.4–3.5, 0.5–0.9, 2.2–4.5. Bottom water temperature, salinity, sediment chlorophyll a concentration, and water content were the most important environmental factors influencing macrofaunal assemblages. Highlights: A total of 112 species were found in seagrass meadows and 74 in neighboring seabed. Dominant species in seagrass meadows were different with neighboring seabeds. Factors influencing macrofauna in seagrass and neighboring seabeds were similar. Temperature and Chl-a were important influencing factors for macrofauna in spring. Sediment water content, salinity had the greatest effects on macrofauna in autumn.